2018
DOI: 10.1186/s12889-018-5545-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescribing during pregnancy in a central region of Italy, 2008-2012

Abstract: BackgroundDrug consumption during pregnancy is a matter of concern, especially regarding drugs known or suspected to be teratogens. Little is known about drug use in pregnant women in Italy. The present study is aimed at examining the prevalence, and to detect potential inappropriateness of drug prescribing among pregnant women in Latium, a region of central Italy.MethodsThis retrospective study was conducted on a cohort of women aged 18-45 years who delivered between 2008 and 2012 in public hospitals. Women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 29 publications
4
35
2
Order By: Relevance
“…In terms of drug utilization during first trimester, the most commonly prescribed drugs were analgesics (with special attention to paracetamol) and antibiotics, in line with results of previous studies evaluating drug use during pregnancy . When looking at the secular trends during the study period, we observed a trend towards an increase of overall prescription rates, similar to other studies .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In terms of drug utilization during first trimester, the most commonly prescribed drugs were analgesics (with special attention to paracetamol) and antibiotics, in line with results of previous studies evaluating drug use during pregnancy . When looking at the secular trends during the study period, we observed a trend towards an increase of overall prescription rates, similar to other studies .…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported, in the current study, the use of psychotropics suffered a marked decline within the first trimester compared with pre‐pregnancy period and a slightly decreased in the first trimester during the studied period, with the exception of antiepileptics . Still, we observed a higher proportion of women receiving at least one prescription of benzodiazepines (BZD) during the first trimester than expected . In Spain, there has been an overall increased on BZD prescriptions in the last decade, with an annual increase of 2% to 3% which is also reflected in this specific population.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the average number of medications used anytime in pregnancy increased two-fold during that period 2 . More recent research from different countries has found that medications are widely used during pregnancy, with the prevalence of using at least one drug ranging from 60 to 90 percent, excluding vitamins and minerals [3][4][5] .…”
Section: All Authors Declare No Conflict Of Interestmentioning
confidence: 99%
“…In routinely collected health data, where study samples are more representative of the underlying population, information on pregnancy intention is typically unavailable. Therefore, studies of prescription drug utilisation or safety usually lack information on pregnancy intention [6][7][8]. Further, for pregnancies to appear in routinely collected data and be identified in studies, they need to proceed beyond a certain point, for example week 12 [7], or end in live births [6].…”
Section: Introductionmentioning
confidence: 99%